Mixed finite element formulation enriched by Adomian method for vibration analysis of horizontally curved beams - A. Moslehi Tabar; H. Najafi Dehkordi (Numerical Methods in Civil Engineering, 2017)
Abstract:The vibration analysis of horizontally curved beams is generally led to higher order shape functions using direct finite element method, resulting in more time-consuming computation process. In this paper, the weak-form mixed finite element method was used to reduce the order of shape functions. The shape functions were first considered linear which did not provide adequate accuracy. Accordingly, Adomian decomposition method was employed to enrich the shape functions. As a result, the error percentage reduced significantly. The present method was validated by solving different examples and comparing the results with those reported by other researchers.